OPTIMASI WAKTU PENGONTAKAN PADA MODIFIKASI SINTESIS NANOPARTIKEL PERAK DENGAN L-Sistein - Dwi Sintya Misi Arsita; Alimuddin Alimuddin; Moh. Syaiful Arif (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
Synthesis of L-cysteine ​​modified silver nanoparticles (AgNPs) investigated. The reducing agent used in the synthesis of silver nanoparticles is trisodium citrate. The reaction between silver nitrate and trisodium citrate is indicated by a color change from clear to yellow. AgNPs were prepared with optimum contact time variations. The result of the UV-Vis spectrophotometer characterization showed that L-cysteine ​​modified silver nanoparticles (AgNPs) with an optimum contacting time of 7 hours. L-cysteine ​​modified silver nanoparticles (AgNPs) were applied as colorimetric histamine sensors. Keywords: Silver Nanoparticles (AgNPs), Optimization, UV-Vis Spectrophotometer.